Collaborations Between Multicultural Educators and Archivists: Engaging Students with Multicultural History Through Archival Research Projects. (2nd July 2016) - Fernández, Natalia
ABSTRACT: When multicultural educators and archivists collaborate to design projects that engage students with multicultural history through archival research, students can learn in-depth research skills with primary source documents, creatively share their knowledge, and, on a broader level, engage with their local community history. The projects shared in this article serve as examples of how partnerships between multicultural educators and archivists can occur, the types of projects that can be developed and how they are implemented, and students' responses to their work. The three student projects, including a display, a history guidebook, and an oral history project, are intended to offer a variety of ideas to inspire multicultural educators to reach out to their local archivists to develop archival research projects of their own. And, to promote effective and fruitful partnerships, also included are lessons learned as well as tips for successful collaborations between multicultural educators and archivists.